2022
DOI: 10.5194/acp-2021-1029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards sector-based attribution using intra-city variations in satellite-based emission ratios between CO2 and CO

Abstract: Abstract. Carbon dioxide (CO2) and air pollutants such as carbon monoxide (CO) are co-emitted by many combustion sources. Previous efforts have combined satellite-based observations of multiple tracers to calculate their emission ratio (ER) for inferring combustion efficiency at regional to city scale. Very few studies have focused on burning efficiency at the sub-city scale or related it to emission sectors using space-based observations. Several factors are important for deriving spatially-resolved ERs from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Emerging satellite observations of atmospheric CO 2 , such as NASA Orbiting Carbon Observatory 3 (OCO-3), can provide independent citywide emission estimates (Nassar et al 2017 , Fu et al 2019 , Goldberg et al 2019 , Andrade et al 2022 , Bell et al 2020 , Liu et al 2020 , Ye et al 2020 , Hakkarainen et al 2021 , Kiel et al 2021 , Park et al 2021 , Chevallier et al 2022 , MacDonald et al 2022 ). The major sources of uncertainties in the satellite-based approach are atmospheric transport (wind) and isolating urban enhancement signals from the background level, which is more challenging for the growing season due to active biospheric uptake (Wu et al 2022 ). With further improvements in methodologies, satellite-based estimates could bridge gaps between city inventories and gridded datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging satellite observations of atmospheric CO 2 , such as NASA Orbiting Carbon Observatory 3 (OCO-3), can provide independent citywide emission estimates (Nassar et al 2017 , Fu et al 2019 , Goldberg et al 2019 , Andrade et al 2022 , Bell et al 2020 , Liu et al 2020 , Ye et al 2020 , Hakkarainen et al 2021 , Kiel et al 2021 , Park et al 2021 , Chevallier et al 2022 , MacDonald et al 2022 ). The major sources of uncertainties in the satellite-based approach are atmospheric transport (wind) and isolating urban enhancement signals from the background level, which is more challenging for the growing season due to active biospheric uptake (Wu et al 2022 ). With further improvements in methodologies, satellite-based estimates could bridge gaps between city inventories and gridded datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of biospheric CO 2 fluxes diminishes the ability to estimate anthropogenic CO 2 emissions. Combining additional trace gases that are emitted with CO 2 during combustion (e.g., CO or NO 2 ) can help to infer urban CO 2 emissions (Konovalov et al, 2016;Reuter et al, 2019;Hakkarainen et al, 2021;Park et al, 2021;Wu et al, 2022a), especially during the growing season when the land biosphere absorbs atmospheric CO 2 . Estimating the regional/local atmospheric background CO 2 column concentration is important for quantifying the magnitude of urban enhancements due to net urban emissions, including anthropogenic and biospheric CO 2 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Using a limited number of SAMs, this study reported elevated X CO2 values have a median value of 2 ppm, ranging from 0 to 6 ppm. A recent study has combined OCO-3 X CO2 data with carbon monoxide (CO) retrievals from the TROPOspheric Monitoring Instrument over Los Angeles and Shanghai, Baotou, and Zibo in China to attribute and contrast intra-city gradients of CO 2 using inferred estimates of combustion efficiency (Wu et al, 2022a).…”
mentioning
confidence: 99%
“…As a product of incomplete combustion, the majority of CO in our atmosphere is emitted by anthropogenic sources (like road transport and industry) and fires (Zhong et al, 2017). As these combustion processes also emit CO 2 , better knowledge of CO can support our understanding of CO 2 emissions (Park et al, 2021;Wu et al, 2022). The importance of air pollution, both for health effects and for better understanding of our atmosphere, is reflected in regulations by the European Union requiring the reporting of emissions of both GHG emissions and a large number of air pollutants, including CO, at the facility-level (EUR-Lex, 2006).…”
Section: Introductionmentioning
confidence: 99%